If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 63 = 2X + -19 Reorder the terms: 63 + x = 2X + -19 Reorder the terms: 63 + x = -19 + 2X Solving 63 + x = -19 + 2X Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63' to each side of the equation. 63 + -63 + x = -19 + -63 + 2X Combine like terms: 63 + -63 = 0 0 + x = -19 + -63 + 2X x = -19 + -63 + 2X Combine like terms: -19 + -63 = -82 x = -82 + 2X Simplifying x = -82 + 2X
| x-0.1=8.8 | | 12(x+2)y^2+64(x+2)y-48(x+2)=0 | | 13=.5c | | 427-847=p | | .83x=-0.16 | | 2x-26+x+3=180 | | (3a+2)(3a-4)=0 | | 20+7x=60-3x | | 1.2x=-0.16 | | 7y^2-21y+14= | | x-3*x-3-64=0 | | M=-16-(-16) | | 6p+12+3p-8=22 | | 25x^2y+130xy-120y=0 | | 6(n+2)=60 | | 2(x+9)+4x=-2x+10 | | x^2-17x-110= | | y+4=-7(-1) | | 42-(-91)=k | | P*3m=4a | | 9x^2-12xy-12y^2=0 | | 3x^2-6x=3 | | 3m*p=4a | | 37-Y=10 | | x^2-12x-108= | | 10x^4-37x^3+33x^2=0 | | a-3=25 | | P=3a*4b | | x+(x+2)=18 | | ln(e)=x | | 5m^2-22m-48=0 | | -19-3x=8x+24 |